Implementasi Metode Pembelajaran Brainstorming Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Alisya Rahma, Siti; Ritonga, Supardi (Universitas Majalengka, 2023)
This research aims to determine the implementation of the brainstorming learning method in increasing students' interest in learning in the Class VII Islamic Religious Education subject at SMPN 06 Bengkalis. The method used in this research is a qualitative method with a descriptive analysis research approach. Data collection and processing of observation and interview data. The results of this research are that the implementation of the Brainstorming learning method in increasing students' interest in learning in the class VII Islamic Religious Education subject at SMPN 06 Bengkalis is still 65% which is in the figure range between 56% - 75% which is categorized as sufficient, meaning that the implementation of the Brainstorming learning method in increasing students' interest in learning in the class VII Islamic Religious education subject at SMPN 06 Bengkalis there are still several aspects that have not been implemented and the factors that are quite influential are that students are still shy about expressing opinions, there is a lack of participation students in group discussions and not all students can understand the teacher's explanation.